Activity Based Costing Method As The Basis For Determining Service Rates In The Radiology Unit At Royal Prima Hospital Medan - Tricya Merrina Arts; Chrismis Novalinda Ginting; Rapael Ginting (CV. Inara, 2023)
Determining the tariff for radiology examination services is a very important decision, because it can affect the profitability of a hospital. Activity Based Costing is a system of accumulating costs and charging costs to products using various cost drivers by tracing the costs of each activity and then tracing the costs from activities to products. The purpose of this study was to determine the application of the activity based costing method as an alternative to CT Thorax service rates in the radiology unit at RSU Royal Prima Medan. The data analysis technique used in this study is a non-statistical quantitative analysis technique. Data in the form of numbers obtained from RSU Royal Prima Medan which contains the calculations are then analyzed using the ABC (Activity Based Costing) Implementation theory. The results showed that the unit cost for CT Thorax examination in the radiology unit of RSU Royal Prima Medan using the activity based costing method was Rp. 1,646,693. The real cost of a CT Thorax examination at the radiology unit of the Royal Prima Medan General Hospital is Rp. 1,897,500. There is a difference in the cost of CT Thorax examination at the radiology unit of RSU Royal Prima Medan with unit costs using the activity based costing method and using real cost calculations at RSU Royal Prima Medan with a cost difference of Rp.250,809. The results showed that the unit cost for CT Thorax examination in the radiology unit of RSU Royal Prima Medan using the activity based costing method was Rp. 1,646,693. The real cost of a CT Thorax examination at the radiology unit of the Royal Prima Medan General Hospital is Rp. 1,897,500. There is a difference in the cost of CT Thorax examination at the radiology unit of RSU Royal Prima Medan with unit costs using the activity based costing method and using real cost calculations at RSU Royal Prima Medan with a cost difference of Rp.250,809. The results showed that the unit cost for CT Thorax examination in the radiology unit of RSU Royal Prima Medan using the activity based costing method was Rp. 1,646,693. The real cost of a CT Thorax examination at the radiology unit of the Royal Prima Medan General Hospital is Rp. 1,897,500. There is a difference in the cost of CT Thorax examination at the radiology unit of RSU Royal Prima Medan with unit costs using the activity based costing method and using real cost calculations at RSU Royal Prima Medan with a cost difference of Rp.250,809.